Determinan Perilaku SADARI di Gampong Bak Buloh Kecamatan Kuta Baro Aceh Besar - Cut Oktaviyana; Dewi Sartika; Cut Rara Hasyiana; Riska Azzafira (Calory Journal Medical Laboratory Journal, 2024)
The increasing prevalence of breast cancer, which continues to rise annually, presents a significant threat to women, including adolescents. Adolescents experience rapid physical development, especially in the breast area. Early detection of breast cancer through regular breast self-examination (BSE) is crucial for this age group. This study aimed to identify the factors (knowledge, attitude, and support from healthcare providers) that influence BSE behavior among adolescents in Gampong Bak Buloh, Kuta Baro District, Aceh Besar Regency. Using a cross-sectional design and a purposive sample of 40 adolescents, the study found that a positive attitude had a 22% greater impact on BSE behavior compared to a negative attitude, while knowledge and support from healthcare providers equally influenced BSE behavior by 16%. It's crucial for healthcare providers to regularly promote BSE to empower both adolescents and adult women to detect breast cancer early, thus enabling prompt treatment.